2018
DOI: 10.3389/fendo.2018.00064
|View full text |Cite
|
Sign up to set email alerts
|

Organotin Exposure and Vertebrate Reproduction: A Review

Abstract: Organotin (OTs) compounds are organometallic compounds that are widely used in industry, such as in the manufacture of plastics, pesticides, paints, and others. OTs are released into the environment by anthropogenic actions, leading to contact with aquatic and terrestrial organisms that occur in animal feeding. Although OTs are degraded environmentally, reports have shown the effects of this contamination over the years because it can affect organisms of different trophic levels. OTs act as endocrine-disruptin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 56 publications
(128 reference statements)
0
19
0
Order By: Relevance
“…Recent findings have shown biologically significant effect of organotins in human blood samples from the USA, and Finland, as well as in human liver from Poland (Barbosa, Ferrão, & Graceli, 2018). Several investigations have revealed that seafood is the primary source of human exposure to organotin compounds (de Araújo et al, 2018). This could be attributed to TBT leach from antifouling paints from commercial vessels and/or due to the persistence of TBT in sediments.…”
Section: Organotinsmentioning
confidence: 99%
“…Recent findings have shown biologically significant effect of organotins in human blood samples from the USA, and Finland, as well as in human liver from Poland (Barbosa, Ferrão, & Graceli, 2018). Several investigations have revealed that seafood is the primary source of human exposure to organotin compounds (de Araújo et al, 2018). This could be attributed to TBT leach from antifouling paints from commercial vessels and/or due to the persistence of TBT in sediments.…”
Section: Organotinsmentioning
confidence: 99%
“…Here, we focused on the prototypical obesogen tributyltin chloride (TBT), a tin-containing chemical (in the organotin class, together with other tributyltin derivatives, [8,9]) that is used as fungicide and heat stabilizer in compositions of polyvinyl chloride, and, along with its metabolites, has been detected in human blood and liver [10,11]. TBT acts as an agonist for two nuclear hormone receptors (NRs), RXRA and PPARG, and, through changes in gene expression, stimulates adipogenesis by inducing their differentiation from pre-adipocytes and/or from mesenchymal stem cells [1215].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, OTCs are a diverse group of widely distributed environmental pollutants and regarded as one of the most toxic anthropogenic pollutants ever purposely introduced into the marine environment . The OTCs are classed as endocrine‐disrupting chemicals, which might be a significant risk to humans and living organisms . They are the most important cause of imposex in dogwhelk, oyster shell malformation and mussel larvae mortality, which has been described in more than one 100 marine species, even at very low concentrations in water (1–2 ng L −1 ) .…”
Section: Introductionmentioning
confidence: 99%